2020
DOI: 10.1136/bmjopen-2020-037613
|View full text |Cite
|
Sign up to set email alerts
|

Are lifestyle pattern changes associated to poor subjective sleep quality?: a cross-sectional study by gender among the general Japanese population underwent specified medical check-ups in 2014 and 2015

Abstract: ObjectivesSubjective sleep quality (SSQ) is defined by the satisfaction of one’s overall sleep experience and is composed of sleep depth and restfulness. It has not been clarified how poor SSQ is associated to changes in lifestyles. The purpose is to reveal the association of lifestyle pattern changes and poor SSQ.DesignA cross-sectional study.SettingThe data on basic attributes, SSQ and lifestyle such as presence/absence of smoking, exercise, physical activity, supper time close to bedtime, drinking habits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…However, interestingly, there was also a correlation between desiring a healthier lifestyle (identified as an interest in quitting smoking and consideration for reducing alcohol intake) and work habits or sleep satisfaction level. This is in line with findings from Hidaka et al [ 39 ], who observed a positive correlation between low sleep satisfaction and unhealthy lifestyle patterns in the Japanese population. FA produced similar results, identifying 1 factor in particular for sleep-related questions and another factor for general well-being.…”
Section: Discussionsupporting
confidence: 93%
“…However, interestingly, there was also a correlation between desiring a healthier lifestyle (identified as an interest in quitting smoking and consideration for reducing alcohol intake) and work habits or sleep satisfaction level. This is in line with findings from Hidaka et al [ 39 ], who observed a positive correlation between low sleep satisfaction and unhealthy lifestyle patterns in the Japanese population. FA produced similar results, identifying 1 factor in particular for sleep-related questions and another factor for general well-being.…”
Section: Discussionsupporting
confidence: 93%